ADAPTASI BUDAYA DAN ISLAM PROGRESIF: PERAN MUHAMMADIYAH DALAM TRANSFORMASI MASYARAKAT JAWA - Harli Selian; Rinaldi; Desi Asmaret; Dasrizal Dahlan (Program Studi Manajemen Pendidikan Islam, 2023)
Muhammadiyah, as a modernist Islamic organization in Indonesia, has significantly contributed to transforming Javanese society since its founding in 1912 by KH Ahmad Dahlan. This article explores how Muhammadiyah addresses the complexities of local cultural dynamics through cultural adaptation and a progressive approach. Grounded in pure Islamic values, Muhammadiyah leverages positive cultural aspects, such as communal cooperation (gotong-royong), to strengthen its mission. Its strategies include modern education, religious practice reforms, and inclusivity principles, creating harmony between Javanese traditions and Islamic teachings. This study employs a descriptive-qualitative analysis with a historical approach to investigate Muhammadiyah's contributions in education, health, economic empowerment, and women's roles through Aisyiyah. The findings reveal that Muhammadiyah not only succeeded in purifying Islamic teachings but also built a more progressive, tolerant, and inclusive society. By emphasizing contextualization, Muhammadiyah created a relevant and adaptive model of Islamic propagation, establishing itself as a symbol of progressive Islam responsive to socio-cultural changes in Java